Framing the Russian-Ukrainian conflict: the role of metaphor, nominalization, and appraisal in shaping media narratives - Judyta Pawliszko, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article investigates how international media outlets frame the Russian-Ukrainian conflict using linguistic strategies such as metaphor, nominalization, and evaluative language. By analysing headlines and subheadings from The New York Times, The Moscow Times, and The Guardian, published between February 24 and March 24, 2022, this study examines how these linguistic devices shape the media’s portrayal of the war, reflect editorial stances, socio-political contexts, and ideological perspectives, and how these elements influence public perception. Drawing on Conceptual Metaphor Theory and Systemic Functional Linguistics (including Appraisal Theory), the study investigates how metaphors (e.g., ECONOMY, STORY/NARRATIVE, JOURNEY, GAME) and evaluative language contribute to the framing of the conflict. The analysis highlights the equally significant roles of metaphor, nominalization, and appraisal in shaping media narratives, demonstrating how political and cultural contexts influence these portrayals. The study concludes by arguing that an integrated analysis of metaphor, nominalization, and appraisal offers a more nuanced understanding of media coverage and its broader implications for public opinion and international relations.